2000
DOI: 10.1067/mhn.2000.104627
|View full text |Cite
|
Sign up to set email alerts
|

Chemoprevention of head and neck cancer

Abstract: 728Increasing emphasis has been placed on chemoprevention as understanding of the genetic and molecular events of carcinogenesis has evolved. More than 1000 compounds that inhibit cancer development in vitro or in animal models have been identified, and active research is under way to determine which of these agents will be both effective and nontoxic in human beings. Currently, 13-cis-retinoic acid is the most studied chemopreventive agent against head and neck cancers. Unfortunately, this vitamin A derivativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 64 publications
(77 reference statements)
0
7
0
Order By: Relevance
“…A common feature of the 5 methylation signature genes identified in our study is their involvement in tissue development and regeneration, and 4 of them, ALDH1A2, OSR2, GATA4, and IRX4, are related to retinoid metabolism and signaling (25,26,(68)(69)(70)(71)(72)(73)(74). Since retinoic acids exert potent effects on cell growth, differentiation, and apoptosis, targeting one or a combination of the 4 genes and thereby modulating retinoid metabolism and signaling may offer novel avenues in successful treatment of OPSCC (75,76). Interestingly, a recent study demonstrated that a retinoic acid-rich tumor microenvironment is required for cytotoxic T cell accumulation accompanied by protective antitumor immunity (77), and it is worth mentioning that an improved clinical outcome of OPSCC patients has been shown to be associated with increased amounts of peripheral and tumor infiltrating T cells (78,79).…”
Section: Discussionmentioning
confidence: 99%
“…A common feature of the 5 methylation signature genes identified in our study is their involvement in tissue development and regeneration, and 4 of them, ALDH1A2, OSR2, GATA4, and IRX4, are related to retinoid metabolism and signaling (25,26,(68)(69)(70)(71)(72)(73)(74). Since retinoic acids exert potent effects on cell growth, differentiation, and apoptosis, targeting one or a combination of the 4 genes and thereby modulating retinoid metabolism and signaling may offer novel avenues in successful treatment of OPSCC (75,76). Interestingly, a recent study demonstrated that a retinoic acid-rich tumor microenvironment is required for cytotoxic T cell accumulation accompanied by protective antitumor immunity (77), and it is worth mentioning that an improved clinical outcome of OPSCC patients has been shown to be associated with increased amounts of peripheral and tumor infiltrating T cells (78,79).…”
Section: Discussionmentioning
confidence: 99%
“…9 However, despite the success of retinoic acid, it was found that, once the drug was discontinued, the lesions had the potential to return. 9 Further, there are limiting toxicities of retinoic acid which make lifelong compliance difficult to ensure. 9 Dry skin, conjunctivitis, mucositis, and appetite loss are a few of the more significant toxicities.…”
Section: Discussionmentioning
confidence: 99%
“…9 Further, there are limiting toxicities of retinoic acid which make lifelong compliance difficult to ensure. 9 Dry skin, conjunctivitis, mucositis, and appetite loss are a few of the more significant toxicities. 1,4,5,9 Nevertheless, for head and neck cancers, retinoic acid remains the most studied and efficacious chemopreventive agent, and is currently the gold standard to which all other promising alternatives should be compared.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations